Complete chloroplast genome of Saussurea inversa (Asteraceae) and phylogenetic analysis. Issue 1 (2nd January 2021) - Wang, Jun; He, Rui; Zhang, Huixuan; Hu, Yanping; Wang, Jianke; Wang, Li; Li, Yi
Abstract: Saussurea inversa Raab-Straube is a small perennial and polycarpic herb that is distributed on the rocky slopes of the Qinghai-Tibetan plateau (QTP) at an altitude of 3700–5400 meters. It has a chloroplast genome structure similar to that of other species of Saussurea . It is 152, 102 bp in size, including a large single-copy (LSC) region of 83, 450 bp, a small single-copy (SSC) region of 18, 286 bp and a pair of inverted repeats (IRs) of 25, 183 bp. The chloroplast genome of S. inversa encodes 113 genes, containing 80 protein-coding genes (PCGs), 29 tRNA and four rRNA genes. Phylogenetic analysis shows that S. inversa is clustered with S. pseudosimpsoniana and S. laniceps .